Pengaruh literasi keuangan dan penggunaan pembayaran digital terhadap perilaku keuangan konsumen generasi z - azaludin, shofi shofi azaludin (Maliki Interdisciplinary Journal, 2025)
This study examined how the millennial generation in North Bekasi used financial literacy, performance expectations, effort expectations, and money savings to make financial technology decisions. The subject of this quantitative study is a millennial employee in North Bekasi who uses financial technologies to make decisions. Purposive sampling combined with a non-probability sampling methodology was used in this study. In this study, 152 respondents served as the sample size. This study’s strategy involves testing hypotheses using SmartPLS 4.0, a structural equation model (SEM). The findings of this research explain how the financial literacy variable influences decisions about financial technology use, as well as how performance expectancy, effort expectancy, and money savings all influence decisions about financial technology use.